2013
DOI: 10.2147/ijn.s44238
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles and magnetic field exposure promote functional recovery by attenuating free radical-induced damage in rats with spinal cord transection

Abstract: Background: Iron oxide nanoparticles (IONPs) can attenuate oxidative stress in a neutral pH environment in vitro. In combination with an external electromagnetic field, they can also facilitate axon regeneration. The present study demonstrates the in vivo potential of IONPs to recover functional deficits in rats with complete spinal cord injury. Methods: The spinal cord was completely transected at the T11 vertebra in male albino Wistar rats. Iron oxide nanoparticle solution (25 µg/mL) embedded in 3% agarose g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Second, oxygen free radicals nonenzymatically catalyze a reaction changing procollagen to collagen in the absence of the rate-limiting enzyme hydroxylase [ 37 ]. Consistent with this, a previous study [ 38 ] reported that eliminating free radicals in local tissue will inhibit scar formation.…”
Section: Discussionsupporting
confidence: 83%
“…Second, oxygen free radicals nonenzymatically catalyze a reaction changing procollagen to collagen in the absence of the rate-limiting enzyme hydroxylase [ 37 ]. Consistent with this, a previous study [ 38 ] reported that eliminating free radicals in local tissue will inhibit scar formation.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, nanoparticles with antigen capable of inducing myelin-specific tolerance could be used to alleviate the chronic inflammatory phase of SCI, which is characterized by unfettered demyelination comparable to EAE models [Jones, 2014]. Other particles, including iron oxide [Pal et al, 2013], gold [Hutter et al, 2010], and quantum dots [Minami et al, 2012; Moquin et al, 2015] have also been used to target microglia and reducing inflammation using in vitro models.…”
Section: Biomaterialsmentioning
confidence: 99%
“…This group also exhibited spontaneous bladder evacuation after 11 d, significantly earlier than any of the other groups. This study also showed that SPION exposure to the glioblastoma U87 cell line with a hydrogen peroxide insult improved cell viability from 44 to 75%, demonstrating the antioxidant effects of the particles (Pal et al, 2013). These two studies show the promise of MNPs for drug delivery after SCI, but more work is needed to understand the mechanisms behind magnetic field stimulation in addition to MNP delivery.…”
Section: Magnetic Drug and Gene Delivery Systems For Promoting Neuralmentioning
confidence: 68%